Formulasi dan Evaluasi Sediaan Nanomouthwash Ekstrak Rimpang Kunyit (Curcuma domesticaVal.) Sebagai Pengobatan Sariawan - Noval Noval; Giovanni Ulima Nibras Giovanni; Tuti Alawiyah Tuti (Program Studi Farmasi Fakultas Sains Kesehatan, 2022)
Background: Turmeric rhizome extract (Curcuma domestica Val.) is a plant that contains curcumin compounds that have the potential to be antioxy and useful for healing canker sores. Current pharmaceutical technology continues to develop, one of which is in particles that are made smaller into nanoparticles as a drug delivery system where the particle size or globule that is reduced in the mouthwash is changed to be smaller and called nanomouthwash to improve the quality of absropsy in the use of mouthwash. Objective: : Knowing the physical quality of nanomouthwash preparations from turmeric rhizome extract (Curcuma domestica Val.) as a treatment of thrush and knowing the stability of the formulation of nanomouthwash preparations from turmeric rhizome extract as a treatment of Ulce.. Methods: The research method used is quasi-experimental time series design. nanomouthwash preparations of turmeric rhizome extract are made in 1 formulation with an extract concentration of 6.96 grams with Characteristic Evaluation and Physical Evaluation. Result: Evaluation of Characteristics which includes Evaluation of Particle Size worth 20.4 nm, PI worth 0.39 and Zeta Potential -5.5 mV while in Physical Evaluation obtained results which include Evaluation of Organoleptical, pH, Homogeneity and Viscosity have been appropriate in Stability Tests at room temperature and cold temperature. Conclusion: : Characteristic Evaluation and Physical Evaluation get the appropriate results and Stability Tests at room temperature and cold temperatures have an effect on pH and Viscosity evaluations, especially on days 14 and 21.